2019
DOI: 10.1128/jvi.00576-19
|View full text |Cite
|
Sign up to set email alerts
|

Senecavirus-Specific Recombination Assays Reveal the Intimate Link between Polymerase Fidelity and RNA Recombination

Abstract: Senecavirus A (SVA) is a reemerging virus, and recent evidence has emphasized the importance of SVA recombination in vivo on virus evolution. In this study, we report the development of an infectious cDNA clone for the SVA/HLJ/CHA/2016 strain. We used this strain to develop a reporter virus expressing enhanced green fluorescent protein (eGFP), which we then used to screen for a recombination-deficient SVA by an eGFP retention assay. Sequencing of the virus that retained the eGFP following passage allowed us to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 63 publications
0
37
0
Order By: Relevance
“…We and others have observed correlations between RdRp fidelity and recombination efficiency, with higher fidelity suppressing recombination and vice versa [19][20][21][22][23][24]. An unexpected outcome of this study was the observation that IF-KH and PS-KH PVs exhibit substantially different propensities for recombination in cells ( Figure 3B), in spite of very similar speed and fidelity phenotypes in cells ( Figures 1C and 2C) and in vitro ( Figure 2D).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…We and others have observed correlations between RdRp fidelity and recombination efficiency, with higher fidelity suppressing recombination and vice versa [19][20][21][22][23][24]. An unexpected outcome of this study was the observation that IF-KH and PS-KH PVs exhibit substantially different propensities for recombination in cells ( Figure 3B), in spite of very similar speed and fidelity phenotypes in cells ( Figures 1C and 2C) and in vitro ( Figure 2D).…”
Section: Discussionmentioning
confidence: 52%
“…Our laboratory has had a longstanding interest in the mechanism of recombination [19,20,23,32,45]. We have shown that the high poly (rU) polymerase activity of PV RdRp derives from template switching during elongation, thus mimicking copy-choice recombination ( Figure 4A) [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, a connection has been made between RdRp fidelity and recombination 14,32,39,41,42 . With more incorporation errors and/or consumption of nucleotide analogues by the RdRp comes an increase in the frequency of recombination both in cells and in test tubes 39 .…”
Section: Discussionmentioning
confidence: 99%
“…So, is it the increased fidelity or decreased speed of nucleotide addition that gives rise to the attenuated phenotype? Further complicating the fidelity-versus-speed question are the recent observations that changes to fidelity also have consequence for the efficiency of recombination (18-23). Increased RdRp fidelity decreases recombination efficiency and vice versa (18-23).…”
Section: Introductionmentioning
confidence: 99%